On the Role of YMCA in Breeding and Boosting Social Morality in Modern China: A Case Study of YMCA of Guangzhou - ZHENG Liqun, (Journal of Research for Christianity in China (JRCC), 2025)
The building of social morality is an important part of morality construction in a modern society. However, since the idea of social ethics was introduced into China from Japan in early 20th Century, the development of its meaning has been showing two directions: one is the national morality oriented to the whole nationality, and the other is the social nationality supported by social life. The two kinds of moral values, one explicit and the other implicit, constituted the basic path of social morality development in modern China. Besides, as China is traditionally in lack of moral resources formed by the civil society, social morality building becomes especially difficult in modern China. However, when a fad of society establishment emerged in late Qing Dynasty and the early Republic of China era, the rapid growth of public space entail the urgent need of corresponding social morality on people. It’s in the context that YMCA, originated from a civil and industrial society under high development in the West, served as the social morality resource in absence in China, through its ideas of social morality and religious morality and its practices of social services, thus making an important breeder and booster of public morality of citizens during the Republic of China era. Taking YMCA of Guangzhou as an example, the paper will demonstrate the argument from two aspects: one is to foster high-level public morality, and the other is to erase unhealthy moral ideas and practices.  About the former, YMCA of Guangzhou set up social morality rules for people and rules for law-executors with the identity of a lawmaker and law-executor, thus making significant contributions to social morality breeding in Chinese society. About the latter, YMCA cooperated with 57 other groups in Guangzhou to assist the government to settle a ban on gambling with success, by virtue of its powerful organization and implementation; it also played an important role in wiping out unhealthy moral ideas and deeds by assisting the government in banning prostitution or offering campaigns to enlighten the public about sexually transmitted diseases. In a word, as a group centered at Christianity, YMCA made a model not only in breeding social morality in China but in wiping out unhealthy morality, thanks to its innate ideas of social morality and religious morality endowed by the Western world, as well as its power in implementation as an organization.